The Dynamics of Co-orbital Giant Exomoons -- Applications for the Kepler-1625 b and Kepler-1708 b Satellite Systems - Moraes, Ricardo; Borderes-Motta, Gabriel; Othon Cabo Winter; Daniela Cardozo Mourão (arXiv.org, 2023)
Exomoons are a missing piece of exoplanetary science. Recently, two promising candidates were proposed, Kepler-1625 b-I and Kepler-1708 b-I. While the latter still lacks a dynamical analysis of its stability, Kepler-1625 b-I has already been the subject of several studies regarding its stability and origin. Moreover, previous works have shown that this satellite system could harbour at least two stable massive moons. Motivated by these results, we explored the stability of co-orbital exomoons using the candidates Kepler-1625 b-I and Kepler-1708 b-I as case studies. To do so, we performed numerical simulations of systems composed of the star, planet, and the co-orbital pair formed by the proposed candidates and another massive body. For the additional satellite, we varied its mass and size from a Mars-like to the case where both satellites have the same physical characteristics. We investigated the co-orbital region around the Lagrangian equilibrium point \(L_4\) of the system, setting the orbital separation between the satellites from \(θ_{min} = 30^{°}\) to \(θ_{max} = 90^{°}\). Our results show that stability islands are possible in the co-orbital region of Kepler-1708 b-I as a function of the co-orbital companion's mass and angular separation. Also, we identified that resonances of librational frequencies, especially the 2:1 resonance, can constrain the mass of the co-orbital companion. On the other hand, we found that the proximity between the host planet and the star makes the co-orbital region around Kepler-1625 b-I unstable for a massive companion. Finally, we provide TTV profiles for a planet orbited by co-orbital exomoons.